Letter to Leona Hudson from Dugald Hudson, August 10, 1944 - Hudson, Dugald (Valdosta State University Archives and Special Collections, 1944)
Letter to Leona Hudson from Dugald Hudson, August 10, 1944 to February 3, 1945. (1944-08-10, 1944-11-21, 1945-02-03). To: Strickland, Leona (Valdosta, GA) From: Hudson, Dugald Names in the Letter: Description: Dugald describes a snowball fight he had with fellow soldiers. He also describes opening his Christmas present from Leona. Original Label: 16.
1 Electronic record(s) and derivatives. `hudson_letter_1651.pdf` 3 pages. 1808184 bytes. MD5: D51A7A41469519A01CFB8D0D279E6E74
Keywords: Letters; Hudson, Dugald; Hudson, Leona